Growth and Development of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) Fed on Artificial Diets Enriched with Wild Host Plants - Rindiani, Dellania Eka; Herlinda, Siti; Suwandi, Suwandi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The quality of artificial diets is important to produce high quality cultures of S. frugiperda. The research aimed to determine the effect of artificial diets based on wild plants on the growth and development of Spodoptera frugiperda. The plants used for enriching artificial diets were Zea mays (control), Ipomoea aquatic, Ipomoea reptans, Amaranthus hybridus, Morus rubra, Brachiaria mutica, and Setaria sphacelata. The results showed that S. frugiperda larvae consuming artificial diets enriched with A. hybridus, Z. mays, I. reptans, and I. aquatic leaves had higher body weight, lower larval mortality and abnormal pupae compared to those of B. mutica, S. sphacelata and M. rubra leaves. The adult females from larvae-consuming diets enriched with A. hybridus, Z. mays, I. reptans, I. aquatica, and S. sphacelata leaves had higher fecundity compared to those of other diets. However, diet enriched with S. sphacelata leaves caused higher larval mortality. Thus, the more suitable diets to increase the larval growth and survival, and adult emergence and fecundity were the diets enriched with wild host plants (A. hybridus, I. reptans, and I. aquatic leaves). Using weed or wild host plant leaves to produce artificial diets is feasible for mass-rearing S. frugiperda.